Distribution In Islamic Economics: An Analysis of Regulation and Supervision from a Microeconomic Perspective - Dina Mariana Ulpah; Irdan Nurdiansyah; Raaf Syamjani; Ahmad Iqbal Nugraha (Jurnal Abdimas Peradaban, 2026)
The objective of this journal is to analyze the regulation and supervision of the distribution of goods and services from a micro level Islamic economic perspective. This study employs a qualitative descriptive method, systematically and coherently structured, using data obtained through library research, including books, journal articles, and credible online sources. The findings reveal that distribution in Islam is founded upon two core principles: the principle of justice and the principle of freedom. The regulatory and supervisory framework for distribution is reflected in the provisions of Fiqh Muamalah, which include the prohibition of ikhtikar (hoarding), guidelines for reasonable profit, equitable distribution, social justice, and the prohibition of monopoly. Islam instructs individuals to manage, allocate, and distribute wealth fairly and proportionally to those in need, thereby preventing the concentration of wealth within a particular group.